2009
DOI: 10.1590/s1413-35552009005000005
|View full text |Cite
|
Sign up to set email alerts
|

Implicações da lipoclasia dermossônica no metabolismo energético e na composição corporal de ratos Wistar saudáveis

Abstract: Implications of dermosonic lipoclasisfor energy metabolism and body composition of healthy Wistar rats Implicações da lipoclasia dermossônica no metabolismo energético e na composição corporal de ratos Wistar saudáveis Gonçalves WLS, Cirqueira JP, Abreu GR, Moysés MR AbstractObjectives: To investigate the implications of Dermosonic lipoclasis (DLC), i.e. lipolysis on subcutaneous white adipose tissue induced by ultrasound, for the energy metabolism and body composition of healthy rats. Methods: Twenty four-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…3,14 This study demonstrated that a single application was able to significantly reduce gluteal-femoral WAT, leading to acute alterations in the energetic metabolism homeostasis. The alterations were mainly in glucose uptake by cells and tissues, and there was an increase in the inflammatory response by high levels of CRP and LDH.…”
Section: Discussionmentioning
confidence: 77%
“…3,14 This study demonstrated that a single application was able to significantly reduce gluteal-femoral WAT, leading to acute alterations in the energetic metabolism homeostasis. The alterations were mainly in glucose uptake by cells and tissues, and there was an increase in the inflammatory response by high levels of CRP and LDH.…”
Section: Discussionmentioning
confidence: 77%
“…[17][18][19][20][21][22] LIUST has been shown to modify cellular and humoral signaling factors, especially the bioavailability of nitrous oxide, thereby regulating interstitial permeability and tissue fluid balance; 9,12,13,29 this in turn results in decongestion of the nasopharyngeal mucosa, regression of interstitial edema and of nasal obstruction/congestion in patients with chronic rhinosinusitis. Supporting this assumption, recent reports in the literature have shown strong correlations among nasal mucosa congestion rates, fibrosis, and vascular density in patients with chronic rhinosinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…Pulsed ultrasound waves act on a cell and/or molecular level by altering membrane permeability, ionic concentration gradients and cell biochemical activity. [14][15][16][17] More recently, ultrasound has been employed as adjuvant therapy in several conditions such as tissue repair, 16 reduction of muscle and joint pain, 17,18 modulation of inflammation, 19,[20][21][22] and reduction of tendon adhesions. [17][18][19] A few studies have demonstrated that LIUST-induced accelerated skin tissue repair results from local modulation of cell mediators/signalers such as nitric oxide, histamine and other cytokines that are involved in inflammation in healing; it also increases the number of fibroblasts and collagen synthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gonçalves e cols. (2009) concluíram que a terapia ultrassônica induziu a redução da ingestão de comida e o peso corporal e deposição de gordura infra-abdominal de 10 ratos Wistar tratados com ultrassom de 3 MHz, com intensidade de 1 W/cm² por 3 minutos, por 10 dias com intervalo de 2 dias a cada cinco aplicações (22).…”
Section: Massagem Modeladoraunclassified